Impact of osteosarcopenia on disability and mortality among Japanese older adults. Issue 2 (1st March 2023) - Shimada, Hiroyuki; Suzuki, Takao; Doi, Takehiko; Lee, Sangyoon; Nakakubo, Sho; Makino, Keitaro; Arai, Hidenori
Abstract: Background: In clinical settings, muscle mass and bone mineral density assessments are usually performed using dual‐energy X‐ray absorptiometry (DXA), the clinical standard technique. However, DXA is often unavailable in community settings. This study aimed to determine whether osteoporosis, osteopenia (OP) and sarcopenia (SP) identified by simplified instruments are associated with the future incidence of disability and mortality and evaluate the validity of these instruments as community screening tools. We also examined osteosarcopenia (OS), defined as the coexistence of OP and SP, as a new indicator of geriatric syndromes to determine whether it has an additive effect on adverse outcome incidence compared with OP and SP alone. Methods: In total, 8995 older adults participated in the study (women: 51.7%, average age: 73.5 ± 5.4 years). Data were extracted from the Japanese national cohort study, National Center for Geriatrics and Gerontology‐Study of Geriatric Syndromes. We determined OP based on T‐scores generated based on the speed of sound, which is the time taken for ultrasound waves to go through a determined distance in the calcaneus bone. Skeletal muscle mass was evaluated using a bioimpedance analysis device. Handgrip strength and walking speed were measured as physical performance indicators. Incidences of disability and mortality were prospectively determined for 5 years. Results: The prevalence of OP, SP and OS was 45.5%, 3.9% and 7.4%, respectively. The incidence of disability in the nonOP/nonSP, OP, SP and OS groups was 6.5%, 14.9%, 20.5% and 33.5%, respectively. The incidence of mortality in the nonOP/nonSP, OP, SP and OS groups was 4.0%, 4.9%, 10.3% and 10.2%, respectively. Participants with OP (hazard ratio [HR]: 1.45, 95% confidence interval [CI]: 1.25–1.68), SP (HR: 1.38, 95% CI: 1.08–1.76) and OS (HR: 1.73, 95% CI: 1.43–2.09) had a higher risk of disability than nonOP/nonSP participants. Participants with OP (HR: 1.31, 95% CI: 1.04–1.64) and OS (HR: 1.45, 95% CI: 1.05–2.00) had a higher risk of mortality than nonOP/nonSP participants. SP was not significantly related to mortality (HR: 1.14, 95% CI: 0.90–1.45). There was no statistical interaction between OP and SP in incident disability and mortality. Conclusions: Among older adults, OS identified by bioimpedance and quantitative ultrasound assessments was associated with an increased risk of disability and mortality. Further research is needed to implement these findings in community health activities, such as setting precise cut‐off values and constructing accurate disability and mortality prediction models.